Lesions of the commissural subnucleus of the nucleus of the solitary tract increase isoproterenol-induced water intake - Blanch, G. T. [UNESP]; Freiria-Oliveira, A. H. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP]; Colombari, Débora Simões de Almeida [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2007)
The nucleus of the solitary tract (NTS) is the primary site of the cardiovascular afferent information about arterial blood pressure and volume. The NTS projects to areas in the central nervous system involved in cardiovascular regulation and hydroelectrolyte balance, such as the anteroventral third ventricle region and the lateral parabrachial nucleus. The aim of the present study was to investigate the effects of electrolytic lesion of the commissural NTS on water and 0.3 M NaCl intake and the cardiovascular responses to subcutaneous injection of isoproterenol. Male Holtzman rats weighing 280 to 320 g were submitted to sham lesion or electrolytic lesion of the commissural NTS (N = 6-15/group). The sham-lesioned rats had the electrode placed along the same coordinates, except that no current was passed. Water intake induced by subcutaneous isoproterenol (30 µg/kg body weight) significantly increased in chronic (15 days) commissural NTS-lesioned rats (to 2.4 ± 0.2 vs sham: 1.9 ± 0.2 mL 100 g body weight-1 60 min-1). Isoproterenol did not induce any sodium intake in sham or in commissural NTS-lesioned rats. The isoproterenol-induced hypotension (sham: -27 ± 4 vs commissural NTS-lesioned rats: -22 ± 4 mmHg/20 min) and tachycardia (sham: 168 ± 10 vs commissural NTS: 144 ± 24 bpm/20 min) were not different between groups. The present results suggest that the commissural NTS is part of an inhibitory neural pathway involved in the control of water intake induced by subcutaneous isoproterenol, and that the overdrinking observed in lesioned rats is not the result of a cardiovascular imbalance in these animals.
Keywords: Nucleus of the solitary tract; Commissural nucleus of the rat solitary tract; Water intake; Arterial pressure; Isoproterenol; Hindbrain